Psychological determination of professional self-improvement of a future teacher (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. This article analyses professional self-improvement as one of thebasic factors of personal growth of a future teacher. The different scientists’approaches to defining the essence of professional self-improvement as apersonally valuable and professionally important quality of a personalitywas considered presenting the main characteristics of this phenomenon. Itwas established that psychological basis of professional self-improvementis professional self-awareness, which contributes to the development of afuture teacher as a subject of professional self-improvement. The mainpsychological determinants of the process of professional self-improvementof a personality and its characteristics were found and presented
Keywords: self-improvement; professional self-improvement; self-knowledge; self-examination; auto-evaluation; self-contro; self-projection